2017
DOI: 10.21037/jtd.2017.09.152
|View full text |Cite
|
Sign up to set email alerts
|

A useful method to keep azygos arch in minimally invasive resection of esophageal leiomyoma

Abstract: Lifting azygos arch with a prolene line is a useful way to keep azygos arch in minimally invasive resection of esophageal leiomyoma without affecting surgical exposure and operative procedure. J Thorac Dis 2017;9(11):4589-4591 jtd.amegroups.com arch. After the azygos vein was fully freed, 4-0 prolene line was threaded through the azygos vein. ENDO CLOSE needle (product number: T173022, COVIDIEN company) was inserted in the posterior axillary line at the fourth intercostal space to catch the prolene line and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In our data, however, no significant relationships were confirmed between these factors and AAP (Supplementary Table 1). AAP during thoracic esophagectomy is an uncommon technique that has been described in only a few publications to date [21,28]. Whether AAP is clinically justified was rarely discussed until the recent study by Fujiwara et al [29], who comparatively analyzed the relationship between surgical outcomes and AAP in 119 patients undergoing MIE for EC and, interestingly, suggested that the achievement of AAP during thoracoscopic esophagectomy might enhance post-surgical urinary output.…”
Section: Jcsmentioning
confidence: 99%
“…In our data, however, no significant relationships were confirmed between these factors and AAP (Supplementary Table 1). AAP during thoracic esophagectomy is an uncommon technique that has been described in only a few publications to date [21,28]. Whether AAP is clinically justified was rarely discussed until the recent study by Fujiwara et al [29], who comparatively analyzed the relationship between surgical outcomes and AAP in 119 patients undergoing MIE for EC and, interestingly, suggested that the achievement of AAP during thoracoscopic esophagectomy might enhance post-surgical urinary output.…”
Section: Jcsmentioning
confidence: 99%